Sistem Informasi Database Akuntansi Laba / Rugi Pada Koperasi Melin Sari Jambi - Rezagi Meilano; Tanto . (Jurnal Inovator, 2018)
This research was conducted at Melin Sari Cooperative which still using manual system. The purpose of this study is to find out how the profit / loss accounting system that runs on the Cooperative Melin Sari and to provide the design of accounting information system profit / loss on the Cooperative Melin Sari. Analyzer used that is including system analysis, which then proceed to stage of system design by using flowchart and DFD. Based on the results of the study the authors found that the system run cooperatives still have shortcomings and weaknesses in terms of member data collection procedures to the transactions performed, documents used, recording loan transactions, and reports generated. Furthermore the authors designed an accounting information system that is able to overcome the weaknesses and shortcomings.